Marital satisfaction and emotional divorce among Iranian married individuals: A survey of hospital visitors of nine provinces - Mohammad Eslami; Mahdieh Yazdanpanah; Parnian Andalib; Azardokth Rahimi; Mansoureh Safizadeh; Adeleh Dadvar; Nouzar Nakhaee (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Evidence is accumulating that the pattern and nature of marital relationships are very different in different cultures. This nationwide study aimed to determine marital satisfaction and the prevalence of emotional divorce as well as to identify the sociodemographic correlates in a Muslim population. MATERIALS AND METHODS: In this cross-sectional study, one-third of Iran's provinces were selected randomly and a representative sample of inhabitants of their central city was included in the study. The ENRICH marital satisfaction scale was used to determine marital satisfaction levels. A single-item measure with confirmed validity and reliability was used to find out about emotional divorce. The demographic variables included respondent's age, spouse's age, gender, educational level, residency, childbearing, and premarriage familiarity. RESULTS: Of the 2033 participants, 1034 were women (50.9%). Nearly one-third of both men and women had academic degrees. Almost 53% of them were satisfied with their marital life and 9.7% had emotional divorce. Men with academic degrees had a higher probability of marital satisfaction (odds ratio [OR] =1.26, 95% confidence interval [CI]: 1.04-1.53) and a lower prevalence of emotional divorce (OR = 0.37, 95% CI: 0.24-0.58). CONCLUSION: This study showed a relatively high percentage of marital dissatisfaction as well as emotional divorce. Policymakers should strengthen premarriage education programs and postmarriage counseling centers.